Implications of the Doctrine of the Kingdom of God for Building a Better Life for People with Disability in Africa: A Case Study of Malawi - Thipa, Joseph A. (Journal of disability & religion, 2016)
African Christian churches, African governments and other institutions, on paper, seem to be determined to support people with disabilities through different programs and institutions. But when it comes to practice, there is very little done in terms of budgeting, funding, and other support. Budgeting, funding, programs and the national laws for people with disabilities-in some countries of Africa-are treated like appendices in terms of their practice. That is, people with disabilities are never treated as deserving the position of core items in national budgets. This article, therefore, constitutes a critical investigation of a theological basis for African Christian believers, African governments, and other institutions to support people with disabilities in the same way God supports them in His kingdom; as evidenced in the New Testament, He puts them at the center of His kingdom. In the course of this investigation, the article will discuss the Kingdom of God now, the Kingdom of God Consummated, and what Jesus says about that Kingdom and people with disabilities, as one who inaugurates it as its King.